Environmental indicators for evaluation of chromium content in soils on the example of an inoperative tanning plant. Issue 8 (17th November 2019) - Mamak, Magdalena; Kicińska, Alicja
Abstract: The main goal of this article was to assess the environmental impact of pollutants from anthropogenic sources (tanning plant) using environmental indicators ( I geo – geoaccumulation index, CF – contamination factor). The assessment was carried out based on the results of total chromium content in soil samples collected in the area of an inoperative tanning plant. Based on the obtained results of total content, significant chromium concentrations were found in the discussed area. All obtained chromium concentrations in the analyzed soil samples exceeded the geochemical background level and the specification limit for group II of soils, i.e. protected areas, defined by a Decree of the Minister of Natural Environment (2016). Based on the obtained results of I geo and CF, the soils in the analyzed area should be considered highly polluted with chromium.